2020
DOI: 10.1039/d0qi00017e
|View full text |Cite
|
Sign up to set email alerts
|

Construction of hierarchical MoSe2@C hollow nanospheres for efficient lithium/sodium ion storage

Abstract: Hierarchical MoSe2@C hollow nanospheres are synthesized via an anion-exchange reaction and exhibit good electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…19 Hou et al reported the use of MoSe 2 @C hollow nanospheres in LIBs, which can achieve a high reversible capacity of 711 mAh g −1 after 300 cycles. 20 Thus, the above results strongly suggest that the morphology design or combining MoSe 2 with carbonaceous materials can enhance the cycle/rate performance of MoSe 2 . However, both excellent rate performance and ultralong cycle life for MoSe combination of the two methods, one can simultaneously achieve outstanding rate performance and ultralong cycle stability for MoSe 2 anodes.…”
Section: ■ Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…19 Hou et al reported the use of MoSe 2 @C hollow nanospheres in LIBs, which can achieve a high reversible capacity of 711 mAh g −1 after 300 cycles. 20 Thus, the above results strongly suggest that the morphology design or combining MoSe 2 with carbonaceous materials can enhance the cycle/rate performance of MoSe 2 . However, both excellent rate performance and ultralong cycle life for MoSe combination of the two methods, one can simultaneously achieve outstanding rate performance and ultralong cycle stability for MoSe 2 anodes.…”
Section: ■ Introductionmentioning
confidence: 78%
“…Structure design and combining MoSe 2 with carbon materials are two effective methods to enhance lithium storage properties. , For example, Wu et al synthesized few-layered MoSe 2 nanosheets via a jet cavitation process, which obviously resulted in enhanced electrochemical performance, especially the rate capability . Hou et al reported the use of MoSe 2 @C hollow nanospheres in LIBs, which can achieve a high reversible capacity of 711 mAh g –1 after 300 cycles . Thus, the above results strongly suggest that the morphology design or combining MoSe 2 with carbonaceous materials can enhance the cycle/rate performance of MoSe 2 .…”
Section: Introductionmentioning
confidence: 96%
“…The sharp weight loss above 300 °C can be divided into two stages, corresponding to the oxidation of VSe 1.6 and MoSe 2 to V 2 O 5 and MoO 3 , which is slightly different from the weight loss of VSe 1.6 /C@N–C and VSe 1.6 /C. 42,43 Based on the weight losses, the carbon contents are calculated to be 39.5%, 47.5%, and 45.7% for VSe 1.6 /C, VSe 1.6 /C@N–C, and VSe 1.6 /C@N–C⊂MoSe 2 , respectively. Through the analysis of the TGA results (provided in the ESI†), the weight contents of VSe 1.6 , MoSe 2 and carbon in the VSe 1.6 /C@N–C⊂MoSe 2 hybrid are estimated to be ∼45.7%, ∼12.9%, and ∼41.4%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, its low theoretical specific capacity (372 mA h g −1 ) cannot meet the rapidly increasing demand for electric vehicles in the vastly emerging market in recent years. 18–23 For large-scale commercial electricity storage, therefore, the performance capability, electrode durability and safety perspective need to be further improved. 24–26 As such, it is urgent to design novel anode materials that possess high theoretical capacities with excellent cycling and rate performance for advanced LIBs.…”
Section: Introductionmentioning
confidence: 99%